Socio-Ecological Systems Analysis and Health System Readiness in Responding to Dengue Epidemics in Ilala and Kinondoni Districts, Tanzania - Mboera, Leonard E. G.; Sindato, Calvin; Mremi, Irene R.; Rumisha, Susan F.; George, Janeth; Ngolongolo, Renfrid; Misinzo, Gerald; Karimuribo, Esron D.; Rweyemamu, Mark M.; Haider, Najmul; Hamid, Muzamil Abdel; Kock, Richard (Frontiers in Tropical Diseases, 2021)
Introduction Since 2010, Tanzania has been experiencing frequent outbreaks of dengue. The objectives of this study were to carry out a socio-ecological systems (SES) analysis to identify risk factors and interventions and assess the readiness of the district in the prevention and control of dengue. Methods The study utilized a cross-sectional purposive selection of key stakeholders responsible for disease surveillance and response in human and animal sectors in Ilala and Kinondoni districts in Tanzania. A SES framework was used to identify drivers and construct perceived thematic causal explanations of the dengue outbreaks in the study districts. A mapping exercise was carried out to analyse the performance of the disease surveillance system at district and facility levels. A semi-structured questionnaire was used to assess the districts’ readiness in the response to dengue outbreak. Results The two districts were characterized by both urban and peri-urban ecosystems, with a mixture of planned and unplanned settlements which support breeding and proliferation of Aedes mosquitoes. The results indicate inadequate levels of readiness in the management and control of dengue outbreaks, in terms of clinical competence, diagnostic capacities, surveillance system and control/prevention measures. Mosquito breeding sites, especially discarded automobile tyres, were reported to be scattered in the districts. Constraining factors in implementing disease surveillance included both intrapersonal and interpersonal factors, lack of case management guidelines, difficult language used in standard case definitions, inadequate laboratory capacity, lack of appropriate rapid response teams, inadequate knowledge on outbreak investigation and inadequate capacities in data management. Conclusion The two districts had limited readiness in the management and control of dengue, in terms of clinical competence, diagnostic capacities, surveillance system and prevention and control measures. These challenges require the immediate attention by the authorities, as they compromise the effectiveness of the national strategy for community health support.